Determinants of Persistent Patterns of Pepino Mosaic Virus Mixed Infections - Alcaide, Cristina; Aranda, Miguel A. (Frontiers in Microbiology, 2021)
Pepino mosaic virus (PepMV) has become a pandemic virus in tomato crops, causing important economic losses worldwide. In Spain, isolates of the EU and CH2 strains co-circulate, with PepMV-EU predominantly found in mixed infections. Simultaneous in planta mixed infections result in an asymmetric antagonism against PepMV-CH2, but the outcome of over-infections has never been tested. PepMV-EU and PepMV-CH2 time-lagged inoculations were performed and viral accumulation was measured 10 days after challenge inoculation. PepMV-EU had a protective effect over PepMV-CH2; in contrast, the accumulation of PepMV-EU increased in plants pre-inoculated with PepMV-CH2 as compared to single infections. We also studied the effect of the type of infection on viral transmission. Independently of the nature of the infection (single or mixed), we observed a strong positive correlation between virus accumulation in the source plant and transmission, excluding mixed infections effects different than modulating viral accumulation. Finally, in order to determine the genetic variability of PepMV strains in single and mixed infections, a 430 nucleotide region was RT-PCR amplified from samples from a serial passages experiment and deep-sequenced. No significant differences were found in the number of nucleotide substitutions between single and mixed infections for PepMV-EU; in contrast, significant differences were found for PepMV-CH2, which was more variable in single than in mixed infections. Comparing PepMV-EU with PepMV-CH2, a higher nucleotide diversity was found for PepMV-CH2. Collectively, our data strongly suggest that PepMV mixed infections can impact the virus epidemiology by modulating in planta virus strain accumulation and diversification.